E-Book Berbasis Elaborasi Gambar Sebagai Penguatan Kognitif Siswa - Prameswari, Jihan; Praherdhiono, Henry; Husna, Arafah (Universitas Negeri Malang, 2022)
The development resulted in an e-book based on image elaboration as a learning medium for cognitive strengthening. Luther-Sutopo's version of the MDLC (Multimedia Development Life Cycle) includes: concept, design, material collecting, assembly, testing, and distribution is a method for development. Data analysis used quantitative and qualitative. The e-book has been declared valid and suitable for use in learning based on the results of the validation of media experts 95.83 percent and material experts 100 percent. Students have stated that ebooks are effective 86.5 percent. E-books provide cognitive reinforcement to students' analytical skills based on increasing pretest and posttest scores.AbstrakPengembangan menghasilkan E-book berbasis elaborasi gambar sebagai media pembelajaran untuk penguatan kognitif. MDLC (Multimedia Development Life Cycle) versi Luther-Sutopo meliputi: Konsep, Desain, Pengumpulan materi, Pembuatan, Pengujian, dan Distribusi merupakan metode untuk pengembangan. Analisis data menggunakan kuantitatif dan kualitatif. E-book telah dinyatakan valid dan layak digunakan dalam pembelajaran berdasarkan hasil validasi ahli media 95.83 persen dan ahli materi 100 persen. Siswa telah menyatakan bahwa ebook efektif 86.5 persen. E-book memberikan penguatan kognitif pada kemampuan analisis siswa berdasarkan peningkatan nilai pretest dan posttest.